2007
DOI: 10.1080/03639040701377847
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Microparticles as Oral Delivery System for Tetanus Toxoid

Abstract: Systemic and local immune response against Chitosan encapsulated tetanus toxoid (CS-TT) microparticles is studied, prepared by ionic cross-linking using Sodium Tripolyphosphate (STPP). Final formulation was evaluated in terms of release of TT in 0.1 N HCl and PBS (pH 7.4), sedimentation profile and stability. CS-TT microparticles, TT in PBS and plain CS microparticles were orally administered to mice and TT (adsorbed) was administered through intramuscular route. Sera were analyzed for anti-TT IgG and intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…On the other hand, IgA levels were not significantly different at day four; however, the levels were significantly (P , 0.01) higher in TT-loaded CMs than in TT in PBS at days eight, 14, and 22. 69 These results suggest that the encapsulated vaccine in CMs enhanced the systemic as well as local immune responses compared to the nonencapsulated vaccine, rendering a safe and effective form of oral vaccination. Further studies on cellular immune responses including memory effect of B-cells and T-cells will ensure the solid effectiveness of CMs for vaccine delivery.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…On the other hand, IgA levels were not significantly different at day four; however, the levels were significantly (P , 0.01) higher in TT-loaded CMs than in TT in PBS at days eight, 14, and 22. 69 These results suggest that the encapsulated vaccine in CMs enhanced the systemic as well as local immune responses compared to the nonencapsulated vaccine, rendering a safe and effective form of oral vaccination. Further studies on cellular immune responses including memory effect of B-cells and T-cells will ensure the solid effectiveness of CMs for vaccine delivery.…”
mentioning
confidence: 72%
“…Several studies have shown that the uptake by M-cells was significantly enhanced and degradation of protein and peptide vaccines in the gastrointestinal track was prevented after the incorporation of vaccine with CMs. 59,[68][69][70][71] Due to its nontoxicity and potent antigen binding properties, chitosan has been considered a promising tool for oral vaccination.…”
Section: Oral Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Particle size measurements can be carried out with commonly used methods such as sieving, microscopy, Coulter counter measurements, laser light-scattering systems or laser light diffraction technique [45][46][47].…”
Section: Particle Size Determinationmentioning
confidence: 99%
“…In a study conducted by Tian et al, fish immunized by oral vaccination with a plasmid DNA (pDNA) containing major capsid protein (MCP) gene of lymphocystis disease virus (LCDV) encapsulated in chitosan microspheres showed significantly enhanced systemic immune responses in comparison with fish vaccinated with naked pDNA [43]. The chitosan encapsulated tetanus toxoid (CS-TT) microparticles have been shown to induce antigen specific IgA in intestinal lavage, faeces, intestinal washings and strong antigen specific IgG in the systemic circulation after oral immunization [44]. Since chitosan polymers have already been used for a variety of biomedical purposes, including the preparation of controlled drug delivery systems, including proteins [45], it was an excellent choice for a vaccine delivery system.…”
Section: Mucoadhesive Microspheresmentioning
confidence: 99%